Smartness in everyday life: Investigating some sociological reasons behind preference of individual interests over collective interests in Tehran metropolis - S.H. Nabavi; F. Salmani (Taḥqīqāt-i Farhangī-i Īrān)
Humans, as social groups, are always interacting with each other to meet their needs. Today, this interaction has encountered with many challenges, with one being the extreme preference of individual and personal interests and ignoring collective ones. In Iranian society, this problem has a long history, but now it has become acute. The main purpose of this research is to investigate the causes of preference of individual over collective interests in everyday life of citizens in Tehran. The survey sample size was estimated to be 385 people through Cochran's formula, and the required data was collected through multi-stage cluster sampling method from regions 1, 7, 11, 14 and 20 of Tehran in the winter of 2019. The explanation was also based on the concepts taken from culture-base theories of Parsons (affective neutrality), Merton (reference group and innovation) and Homans (stimulus proposition) and their synthesis. For this purpose, bivariate and multivariate tests were used. The findings showed that even in the traumatic situation of Covid-19, when according to Durkheim's theories, people should always prioritize collective interests over individual ones; a considerable number of respondents (94%) prioritized individual interests. They prefer collective interests, with market place shrewdness attitude and culture playing a major role. Specifically, it became clear that the higher the emotional neutrality, higher the tendency to reference groups, tendency to innovation, and tendency to stimulus, the preference of individual interests over collective interests.